REMODELING OF THE STRUCTURAL COMPONENTS OF THE SPLEEN CAPSULE IN RATS UNDER THE INFLUENCE OF A COMPLEX OF CHEMICAL FOOD ADDITIVES - Mamai, O.V.; Bilash, S.M.; Pronina, O.M.; Koptev, M.M.; Pirog-Zakaznikova, A.V.; Oliinichenko, Ya.O.; Hrechka, V.V. (World of Medicine and Biology, 2024)
The spleen, although often underestimated, is a particularly important component of the immune system, which some scientists call the “forgotten” organ. Its importance and role, in our opinion, are undoubtedly necessary for maintaining and regulating the body’s immunogenic and protective processes. The spleen plays a key role not only as a universal organ of hematopoiesis in the fetus and ensures the constancy of blood composition and properties, but also as a crucial organ in the process of antigen-dependent differentiation of T- and B-lymphocytes. In addition, the state of the spleen’s connective tissue capsule, which is an integral part of the musculoskeletal system, requires further study to understand the pathophysiological mechanisms of the effect of a complex of chemical food additives on the biological structures of the immune system, which was the purpose of the study. In this study, using histological and morphometric methods of research, the overall average thickness of the spleen connective tissue capsule was determined. It was found that the introduction of a complex of food chemical additives to white experimental rats leads to thinning and destruction of the connective tissue capsule in the early stages and to a significant thickening of the capsule in the later stages due to hyperhydration of the amorphous substance and destruction and swelling of the fibrous component.